LANTHANIDE PICRATE COMPLEXES AND PICRIC ACID ADDUCT OF A CALIX[4]ARENE DIAMIDE - SYNTHESES AND STRUCTURES OF [TM(LH(-2))A], [CE(LH(-2))(MEOH)(2)A]CENTER-DOT-HA, [PRLA(3)] AND L-CENTER-DOT-2HA (L=5,11,17,23-TETRA-TERT-BUTYL-25,27-BIS(DIETHYLCARBAMOYLMETHOXY)-26,28-DIHYDROXYCALIX[4]ARENE, HA=PICRIC ACID) - Beer, P; Drew, M; Grieve, A; Ogden, M (1995)
Reactions of 5,11,17,23-tetra-tert-butyl-25,27-bis(diethylcarbamoylmethoxy)-26,28- dihydroxycalix[4]arene (L) with lanthanide picrates produced 1:1 metal-calixarene complexes incorporating one, two or three picrate moieties, depending on the reaction conditions and the lanthanide used. Dichloromethane solutions of L have been found to extract picric acid (HA) from aqueous solution, resulting in the formation of an L·2HA adduct. Single crystal structure determinations have been carried out on [Tm(LH-2)A]·2.5CH2Cl2, [Ce(LH-2) (MeOH)2A]·HA·H2O, [PrLA3]·2CH2Cl2·1.5H2O and L·2HA·EtOH. The possible variations of these formulae, depending on the charge distribution within the complexes, are discussed. The calixarene is found in a distorted cone conformation in each case. The intense colour of some of these complexes appears to correlate with the disposition of a picrate moiety close to a calixarene phenyl ring, consistent with calixarene→picrate charge-transfer absorption. The UV/VIS spectroscopic studies suggest that at least some aspects of the solid-state structures are maintained in solution.